Proposta de desenvolvimento do jogo "eu me cuido": educação inclusiva em saúde para crianças com síndrome de Down - Andrade, Gustavo de Oliveira (2023)
Digital games are important recreational tools for education, as they are attractive to children. In inclusive education, they are beneficial in facilitating learning, like children with Down Syndrome. These games can fulfill an information role beyond the screens, with attitudinal changes, as in health care learning. This proposal seeks to understand how the interface of games and communication mediated by software can contribute to the education of children with Down Syndrome, in learning about respiratory health care and in the transmission of viral diseases. Therefore, the present study proposes to carry out a qualitative and quantitative systematic review, based on PubMed, LILACS and Scopus databases. We also surveyed the state of the art in the availability of applications and digital games on the topic of respiratory health, through a qualitative study based on the Google Play platform. Based on the surveys carried out, we present a project to develop a serious educational game entitled “Eu me Cuido”, aimed at promoting basic health care, guidance on the correct use of Personal Protective Equipment (PPE) and awareness of the community, both in the context of the pandemic caused by COVID-19 and other viral respiratory diseases. It is expected with the proposition and elaboration of the game a better mediation of educational dialogues with this public. It is also intended that this resource encourage good habits of prevention and basic health care, ensuring that these are incorporated through play and the mimicry of virtual reality into the children's daily lives.